Separation of benzene from alkanes by solvent extraction with 1-ethylpyridinium ethylsulfate ionic liquid - Elena Gómez (2010)
The (liquid + liquid) equilibrium (LLE) data for ternary mixtures {alkane + benzene + 1-ethylpyridinium ethylsulfate ([EPy][EtSO4])} at T = (283.15 and 298.15) K and atmospheric pressure are presented. The alkanes used were hexane and heptane. The cloud point method was used to determinate the binodal curve, and the tie-line compositions were obtained by density measurements. The LLE data obtained were used to calculate distribution coefficients and selectivity values. The consistency of tie-line data was ascertained by applying the Othmer-Tobias and Hand equations. Correlation of the experimental tie-lines was conducted through the use of NRTL equation, which provides good correlation of the experimental data. The results show that [EPy][EtSO4] can be used as an alternative solvent in liquid extraction processes for the removal of benzene from its mixtures with alkanes.